Critical Success Factors For Enhancing The Community Economic Well-Being - Megasari, Rizza; Sahid, Sheerad; Hussin, Muhammad (Social Welfare: Interdisciplinary Approach, 2023)
Well-being is not only defined objectively but also subjectively that refers to the study of happiness and life satisfaction. This study aims to analyze measurement indicators and factors that influence economic well-being based on previous studies discussing economic well-being and the factors that influence it. To provide a systematic review of the literature, we adopted a Prisma-based flowchart model to achieve a deeper understanding. The findings show that the main indicator that is often used in measuring economic well-being is income, followed by wealth, consumption expenditure, employment status, productivity, financial stability, inequality, and education level. This result also confirms that literacy levels such as entrepreneurial literacy, health literacy, food literacy, and financial literacy are factors that affect economic well-being. In addition, life satisfaction with work and education, economic behavior both in consumption and production as well as work-life balance in the division of time for work and other personal matters also affect the level of individual and community economic well-being. From the results of the study obtained, it can contribute to the government as a policy maker to pay attention to the well-being of the community. In addition, it provides another description of the factors that influence economic well-being for further research, like home economic literacy.
Keywords: economic well-being; income; wealth; literacy; life satisfaction; work-life integration